Clinical Evaluation of T-AYU-HM Premium in Sickle cell Anemia Patients: A Retrospective Study (International Journal of Ayurveda and Pharma Research, 2022)
Background: The orphan status of sickle cell invites many researchers toward drug development in the past decade. A substantial number of clinical trials either understudies or in the planning stage focused on sickle cell disease. Sickle cell traits are often considered asymptomatic and the silent condition is associated with diverse complications. Objective: To clinically evaluate the safety and effectiveness of T-AYU-HM Premium Tablets (300mg) in sickle cell anemia patients: an observational retrospective studyMethodology: This is a single-arm case-control retrospective study of sickle cell trait patients admitted to Dhanvantari Clinic from 2018 to 2020. Patients' vital and clinical information based on inclusion and exclusion criteria were collected and analyzed using SPSS software.Result: A total of 100 patients with sickle cell traits were included in the study. The treatment exhibited significant improvement was seen in (P